Globalization and variants of local adaptation: Theory and justification with symbolic logic. (November 2016) - Boone, Christophe; Péli, Gábor
An increasing body of evidence indicates that globalization can trigger a variety of reactions from societies. The possible outcomes include blending, hybridization, fault line formation or even an increased salience of local traditionalist value systems. An important task for the research field is developing systematic, comparative theories predicting which outcome is expected to emerge depending on the interplay between the global and the local. Drawing on the rich empirical literature on globalization variants, the article takes a further step in theory building by proposing a typology with the four possible outcomes mentioned above. To make the model premises more transparent, the authors transcribe their arguments into symbolic logic sentences and derive the typology outcomes as theorems. This allows testing if the proposed model does indeed imply the purported conclusions, and to see what consequences would, or would not, follow from a slightly modified premise set, that is, from a slightly modified globalization theory.